Enantioselective Synthesis of cis and trans 4‐Aminopipecolic Acids as γ‐Amino Acids for the Construction of Cyclic RGD‐Containing Peptidomimetics Antagonists of αVβ3 Integrin. Issue 28 (30th June 2020) - Dordoni, Francesca; Scarpi, Dina; Bianchini, Francesca; Contini, Alessandro; Occhiato, Ernesto G.
Abstract : A stereodivergent strategy to obtain enantiopure cis and trans 4‐aminopipecolic acids (4‐APAs) in a suitably protected form for peptide synthesis has been devised starting from a common, known precursor in turn easily prepared from commercial ( R )‐4‐cyano‐3‐hydroxybutyric acid ethyl ester. The two isomers were efficiently obtained in 40 % and 23 % overall yields, respectively, in seven and ten steps. To demonstrate their usefulness in peptidomimetic synthesis, both 4‐APA isomers were incorporated as γ‐amino acids in a cyclic RGD‐containing sequence, although for the trans 4‐APA isomer a further amino acid in the sequence (L‐Phe) was needed to allow ring closure. The two cyclopeptides were tested as αV β3 integrin antagonists in comparison with cilengitide. Abstract : A stereodivergent preparation of cis and trans 4‐aminopipecolic acids (4‐APAs) was developed from a common precursor to obtain suitably protected, constrained γ‐amino acids useful in peptidomimetic synthesis. Two antagonists of αV β3 integrin were synthesized.